Best management practices for agricultural nonpoint source pollution: Policy interventions and way forward. Issue 2 (28th November 2019) - Jain, Chakresh Kumar; Singh, Surya
Abstract: Best management practices (BMPs) are the tools which are adopted to run any activity while inflicting least negative impacts on the surrounding environment. Since, water pollution is one of the most important issues in today's world; it is indispensable to discuss the activities which are deteriorating its quality. Although, a number of treatment technologies and methods are in place for treating the point sources of pollution, there is a need to address nonpoint sources of pollution. There are many successful practices which are capable of curtailing the impacts of nonpoint source pollution, if adopted. In this paper an attempt has been made to evaluate the performance and trade‐offs of various management practices to address the issues of agricultural nonpoint source pollution. Nevertheless, there is a dearth of guiding principles which can pave a way for adoption of these practices. Therefore, an attempt has also been made to explore the aspects of policy formulations along with emphasizing the factors which can lead to adoption/ non‐adoption of such practices. 摘要: 最佳管理实践（BMPs）是在经营任何活动的同时对周围环境造成最低消极影响而采用的一系列工具。鉴于水污染是当今全球最重要的问题之一，探讨那些恶化水质量的活动是必不可少的。尽管存在一系列处理点源污染的技术和方法，但还需要应对非点源污染。有许多成功实践能减少非点源污染造成的影响，如果这些实践被采纳的话。本文提出一项举措，用于评价不同管理实践的表现和取舍，以期应对农业非点源污染问题。尽管如此，缺乏能帮助采纳这些实践的指导原则。因此，提出了另一举措，探究政策制定的各个方面，并强调那些能导致采纳/不采纳这类实践的因素。 Resumen: Las mejores prácticas de gestión (BMP, por sus siglas en inglés) son las herramientas que se adoptan para ejecutar cualquier actividad y, al mismo tiempo, infligen el menor impacto negativo en el entorno. Desde entonces, la contaminación del agua es uno de los problemas más importantes en el mundo de hoy; Es indispensable discutir las actividades que están deteriorando su calidad. Aunque existen varias tecnologías y métodos de tratamiento para tratar las fuentes puntuales de contaminación, es necesario abordar las fuentes no puntuales de contaminación. Hay muchas prácticas exitosas que son capaces de reducir los impactos de la contaminación de fuentes no puntuales, si se adoptan. En este documento se ha intentado evaluar el desempeño y las compensaciones de varias prácticas de manejo para abordar los problemas de la contaminación de fuentes no puntuales agrícolas. Sin embargo, hay una escasez de principios rectores que pueden allanar el camino para la adopción de estas prácticas. Por lo tanto, también se ha intentado explorar los aspectos de las formulaciones de políticas junto con enfatizar los factores que pueden conducir a la adopción / no adopción de tales prácticas..